Nanoencapsulated Doxorubicin Prevents Mucositis Development in Mice - Cristiane M. Pinto; Laila S. Horta; Amanda P. Soares; Bárbara A. Carvalho; Enio Ferreira; Eduardo B. Lages; Lucas A. M. Ferreira; André A. G. Faraco; Helton C. Santiago; Gisele A. C. Goulart (MDPI AG, 2021)
Doxorubicin (DOX), a chemotherapy drug successfully used in the therapy of various types of cancer, is currently associated with the mucositis development, an inflammation that can cause ulcerative lesions in the mucosa of the gastrointestinal tract, abdominal pain and secondary infections. To increase the safety of the chemotherapy, we loaded DOX into nanostructured lipid carriers (NLCs). The NLC-DOX was characterized by HPLC, DLS, NTA, Zeta potential, FTIR, DSC, TEM and cryogenic-TEM. The ability of NLC-DOX to control the DOX release was evaluated through in vitro release studies. Moreover, the effect of NLC-DOX on intestinal mucosa was compared to a free DOX solution in C57BL/6 mice. The NLC-DOX showed spherical shape, high drug encapsulation efficiency (84.8 ± 4.6%), high drug loading (55.2 ± 3.4 mg/g) and low average diameter (66.0-78.8 nm). The DSC and FTIR analyses showed high interaction between the NLC components, resulting in controlled drug release. Treatment with NLC-DOX attenuated DOX-induced mucositis in mice, improving shortening on villus height and crypt depth, decreased inflammatory parameters, preserved intestinal permeability and increased expression of tight junctions (ZO-1 and Ocludin). These results indicated that encapsulation of DOX in NLCs is viable and reduces the drug toxicity to mucosal structures.